Parametric Experimentation of Output Efficiency of Vibration-Based Impact Mode Piezoelectric Power Generator - Mohd Daud, Mohammad Faisal Afifi; Basari, Amat Amir; Yan, Ng Xue; Ahmad Nawir, Nur Amalina; Hashimoto, Seiji; Ahmad Isira, Ahmad Sadhiqin (International Journal of Integrated Engineering, 2020)
This paper evaluates the output efficiency and the frequency responses of a designed vibration-based impact mode piezoelectric power generator with additional interfaced plate. Indirect impact towards the piezoelectric disc is generated by sandwiching the interfaced plate between the piezoelectric disc and contact structure. The impact force can be varied by altering the bending stress of the beam. The output efficiency of the piezoelectric disc is found to increase about 87% by utilizing 1mm thickness of the vibrating beam compared to 2mm thickness. The output efficiency with the additional interfaced plate can harvest about 3 times higher than that of without the interfaced plate. In order to investigate the influence of the interfaced plate, two variables such as the interfaced plate’s diameter and height are studied. It is confirmed from the experimental results that the output of the piezoelectric disc is to be inversely proportional to the height and also to the diameter of the interfaced plate.